Composition and variability of essential oil in six species of citrus from Sarawak - Trishna Sharma, A\p Matan Komar (Universiti Malaysia Sarawak (UNIMAS), 2014)
A research was carried out to determine the variability and composition of the essential oils from the leaves and peels of six ellnls species which are C hyslrix, C microcarpa, C grandis. C allranlij'ofia. C. sinensis and C. SlIhllensis. These species were collected randomly from the various locations from Sarawak. The essential oils from leaves and peels of Citms species were isolated using hydrodistillation method. The percentage yields of essential oil obtained were ranged from 3.01% to 38.80% for the peels while for leaves ranged from 0.87% to 4.82%. The essential oils obtained were analysed by using Gas Chromatography-Flame Ionization Detector (GC-FID). A total of 67 and 76 chemical constituents were identified from leaf and peel oil, respectively. The main component found in the peel oils of the six Cilms species was (+)-Iimonene ranged from 54.57010 to 98.38%. The major components found in the leaf oils of six Citms species were iethylmethylpyrazine, elemol, (+)-limonene, Iimonene and octenone. The chemical variability between the species were analysed by using Hierarchical Cluster Analysis (HCA). The dendogram showed that leaf oil of C. grandls and C. sllhllensis followed by C. aurantifofia and C. sinensis were shared the similarities of chemical constituents of essential oil. Meanwhile, for the peel oil, the dendogram showed that C. mlcrocarpa. C. sineneis, C. grandis and C. slIhllensis were closely related to each other.